2008
DOI: 10.1177/0042085907311791
|View full text |Cite
|
Sign up to set email alerts
|

Communities, Students, Schools, and School Crime

Abstract: This study investigates how community characteristics, student background, school climate, and zero-tolerance policies interact to affect school crime. The study articulates and fits a school crime model to 712 high schools participating in the 2000 School Survey on Crime and Safety, confirming that school location and student socioeconomic status have moderate effects on school crime. Much of the contextual effects are mediated via school climate. School climate reflected by school size, student mobility, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…The SSOCS, a nationally representative sample of U.S. public schools, is considered one of the richest datasets for studies of school violence. Data from the SSOCS have been used in many published studies throughout the last decade (Chen, 2008;Granberg-Rademacker et al, 2007;Jennings et al, 2011;Kupchik & Ward, 2014;Maskaly, Donner, Lanterman, & Jennings, 2011;O'Neill & McGloin, 2007;Patton, 2011;Phillips et al, 2014). School administrators from elementary, middle, and high schools complete the survey.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SSOCS, a nationally representative sample of U.S. public schools, is considered one of the richest datasets for studies of school violence. Data from the SSOCS have been used in many published studies throughout the last decade (Chen, 2008;Granberg-Rademacker et al, 2007;Jennings et al, 2011;Kupchik & Ward, 2014;Maskaly, Donner, Lanterman, & Jennings, 2011;O'Neill & McGloin, 2007;Patton, 2011;Phillips et al, 2014). School administrators from elementary, middle, and high schools complete the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Studies incorporating multiple crime prevention techniques have also identified several variables as predictors of reduction in school violence including limited class changes (O'Neill & McGloin, 2007), closed campuses (O'Neill & McGloin, 2007), dress codes (Phillips, Turner, & Holt, 2014), identification cards (Phillips et al, 2014), security cameras (GranbergRademacker, Bumgarner, & Johnson, 2007), and uniform policies (Granberg-Rademacker et al, 2007). However, most studies focusing on the effectiveness of school situational crime prevention methods have found few statistically significant effects on violence occurring within the school (Chen, 2008;Cheurprakobkit & Bartsch, 2005;Schreck, Miller, & Gibson, 2003;Tillyer et al, 2011). These conflicted findings are mirrored by the divided viewpoints of administrators (Garcia, 2003) and students (Brown, 2005) about the effectiveness and appropriateness of crime prevention methods employed in the school setting.…”
Section: School Securitymentioning
confidence: 99%
See 2 more Smart Citations
“…Youth often feel less safe in larger schools (Lleras, 2008) perhaps due to the fact that larger schools had higher rates of violence (Ferris & West, 2008), crime (Chen, 2008), and vandalism (Walker & Gresham, 1997) than smaller schools. Academic achievement is another important school characteristic associated with aggression.…”
Section: Distal Microsystem Influences: School and Neighborhood Charamentioning
confidence: 99%